THE IMPORTANCE OF NUTRITIONAL THERAPY IN CHILDREN WITH LEUKEMIA: A SYSTEMATIC REVIEW OF THE LITERATURE - da Silva, Andreina Rocha; dos Santos, Jonatas Lessa; Barbosa, Thaylla Vieira; Ferreira, Thiago Silva (Seven Editora, 2025)
Nutritional therapy in children with leukemia represents a fundamental strategy for clinical recovery and improvement of quality of life. This study aimed to analyze, through an integrative literature review, the importance of nutritional support in childhood cancer treatment. The survey was conducted between January and March 2025, using the Scielo, PubMed, and Google Scholar databases. Initially, 401 articles were identified; After applying inclusion and exclusion criteria, seven studies were selected for critical analysis. The results indicated that adequate nutritional intervention favors the strengthening of the immune system, improves the response to treatment, and reduces the incidence of infectious and nutritional complications. In addition, the risks associated with the treatment, such as loss of lean mass and weight gain, were evidenced, reinforcing the need for continuous nutritional monitoring. It was also observed that the oral route should be stimulated whenever possible, with enteral and parenteral nutrition being indicated in specific cases of greater gastrointestinal involvement. It is concluded that nutritional care, planned in an individualized way, is essential from the time of diagnosis, acting not only in physical support, but also in promoting healthier growth and development during and after cancer treatment. or nutritional risk, due to improved immune function. DOI: https://doi.org/10.56238/sevened2025.018-007